"Know Who They Have in Front of Their Eyes": A Justice as Praxis Paradigm for Teaching and Learning. Issue 2 (April 2020) - Everett, Sakeena
Inequitable access to learning opportunities has intersectional consequences for Black students in general and gifted education. Equally important, all students (regardless of race, ethnicity, gender, socioeconomic class, and grade-level), more often than not, lack invaluable opportunities to learn about the innumerable contributions of students and families of color in the United States and worldwide. To address these injustices, Ladson-Billings advocated for a shift from "justice as theory toward justice as praxis ." In this article, I unpack the components of justice as praxis work, and I discuss how I engaged in this work in my secondary English Language Arts (ELA) classroom. I address the following questions: What does it mean "to be seen" from the perspective of a Black male academically high-achieving student? What is needed for teachers to adopt a justice as praxis paradigm to improve their teaching and learning with students who have not been well served in public schools?